Caudal Epidural Block for Ureteroscopic Lithotripsy (Ursl): A Prospective Study - Bhattarai, Rupak; Paudel, Bandana; Subba, Sangeeta; Das, Chitta Ranjan (Birat Journal of Health Sciences, 2020)
Introduction: Ureteroscopic lithotripsy (URSL) is the surgical treatment of choice for ureter stones. There are lots of anesthetic considerations for removal of such stones. Generally, ureteroscopic lithotripsy are done under general anesthesia and spinal anesthesia. Objectives: The purpose of this study is to assess whether ureteroscopic lithotripsy can be done under caudal anesthesia. Methodology: This prospective observational study was conducted in Nobel Medical college Teaching hospital, Nepal over a period of one and half year from May 2018 to October 2019. All the 100 patients posted for ureteroscopic lithotripsy was given caudal anesthesia. Location of stone, duration of surgery, time of onset of caudal anesthesia, time and level of maximum block spread, Intensity of block was assessed. Result: Out of 100 patients, 56 were male and 44 were female. The mean age and weight was 58±13.182 and 62±18.42 respectively. Time of onset of sensory block, 26 patients in 0- 5 minutes, 26 patients in 5-10 minutes, 56 patients in 10-15 minutes, 12 patients in 15-20 minutes, 4 patients in 20-25 minutes & 2 patients in more than 25 minutes. Maximum spread of block was seen at T6 level in 4 patients, at T8 level in 36 patients and at T10 level in 56 patients. Conclusion: Caudal epidural block is a safe, effective anesthetic technique for ureteroscopic lithotripsy.